3+(-2)-(-4)+5=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 22:34:35
3+(-2)-(-4)+5=3+(-2)-(-4)+5=3+(-2)-(-4)+5=3+(-2)-(-4)+5=3-2+4+5=10原式=3-2+4-5=03+(-2)-(-4)+5=3-2+4+5=
3+(-2)-(-4)+5=
3+(-2)-(-4)+5=
3+(-2)-(-4)+5=
3+(-2)-(-4)+5
=3-2+4+5
=10
原式=3-2+4-5=0
3+(-2)-(-4)+5
=3-2+4+5
=10
3+(-2)-(-4)+5=
4/3×-()=2/5×()=12/7×()=5×()=1
3:(4x+3)=2:(x-5)
2*()=1/4/()=5*()=1/3*()=()
(1-2)(1-3)(3-4)(4-5)...(19-20)=
2/5除以(4/5-3/4)=?能简算就简算
5/4*(-0.6)/(-3的平方)+2/3*(-4/5)=?
4/5=(x-21)/(2x/3 )
(1/3+2/3)+(1/4+2/4+3/4)+(1/5+2/5+3/5+4/5)+.+(1/100+.99/100)=
填---填2+2=1+( )4-1=5-( )5-3=( )-2( )-4=3-2
判断:1/4+2/5+3/5=1/4+(2/5+3/5)对错
3/4×()=2/7÷()=()×0.2=3-()=()+1/5=1
2-(4x+3)=53(2x+1)+4-(2x-5)
(2-3/4)x =4/5
4x-5-3(x-2)=3
(-3/5)×(-12)+0.27×5/9+(-12)×(-2/5)+4/9×0.27=?
(3×4)×(2×5)=(2×5)×(3×4)运用了什么运算定律?
1+(-2)+3+(-4)+5+(-6)+.+(+99)+(-100)=?